The Dilemma Between Fiscal Decentralization and Budget Balance - Jongmin Shon (Transylvanian Review of Administrative Sciences, 2022)
This paper explores the effects of the distribution of fiscal authority for fiscal decentralization on the U.S. state budget balance. Numerous scholars have pointed out that fiscal institutions play an important role in achieving budget balance, but their degree of authority fundamentally determines how fiscal institutions are authorized across the multi-level system in a federal government system. As an empirical exploration, this paper captures the authority of fiscal institutions through multiple dimensions of accounting and financial information. The results revealed that local governments are better able to balance their budgets when fiscal authority over revenue is decentralized, while states are more likely to achieve a balanced budget when authority over expenditure is decentralized. These contradictory effects result from overlapping tax-bases and customers of public services across states and their local governments.